Fabrication of Micropatterned Surfaces by Improved Investment Casting - Schmitz, G. J.; Grohn, M.; Bührig-Polaczek, A. (Advanced engineering materials, 2007)
A defined surface texture in the sense of geometrically, relief‐like functionalized surfaces of macroscopic investment castings has not been subject of research and development so far. As all materials being used in the investment casting procedure (polymers, waxes, ceramics and metals) allow duplicating structures of micron or even submicron size, investment casting of metallic components with finest surface structures should be possible and should lead to an improved functionality of the cast metallic parts. The present paper details the production of metallic parts with micropatterned surfaces and outlines actual limits as well as further developments of the investment casting process.